What motivates people with type 2 diabetes to maintain lifestyle changes and what challenges do they experience? A qualitative evidence synthesis - Tina Bekken; Nina Ottesen; Claire Glenton; Lena Victoria Nordheim (PLoS ONE, 2025)
Background People with type 2 diabetes often find recommended lifestyle changes difficult to achieve and can find it particularly difficult to maintain these changes. It is therefore useful to explore their views and experiences about what influences them when attempting to achieve these goals. Objectives To identify, appraise and synthesise qualitative studies that explore what motivates people with type 2 diabetes to maintain lifestyle changes over time and the challenges they experience. Methods We included qualitative studies and mixed methods studies with a qualitative component, in any language, of adults who had type 2 diabetes and who had maintained lifestyle changes for a minimum of twelve months. We searched MEDLINE, CINAHL, PsycINFO and EMBASE from inception to 4th November 2024. We extracted data using a pre-designed form and assessed methodological limitations using predefined criteria. We used a thematic synthesis approach to analyse the data. We assessed our confidence in the review findings using the GRADE‐CERQual approach. Finally, we used our findings to develop a model using the locus of control theory and to develop implications for practice. Results We included twelve studies from Europe, USA, Canada, South-Africa, Australia and New Zealand. Participants described several factors that motivated them to maintain lifestyle changes, including getting support from others, seeing results from their lifestyle changes, walking as an activity, being physically active with others, fearing the consequences of type 2 diabetes, and taking control. Factors that they viewed as challenging included mental, physical, practical, and social challenges around exercise, and lack of follow-up from healthcare professionals. Conclusions Our review identified several factors that may influence maintenance of lifestyle changes in type 2 diabetes. Based on these findings, we have developed a series of questions to help people with type 2 diabetes and their healthcare providers think about how best to maintain lifestyle choices over time.